JEJAK SEJARAH DAN PENERAPAN TOTAL QUALITY MANAGEMENT: STUDI KASUS DI RA MA'ARIF NU 002 SAMARINDA: STUDI KASUS DI RA MA'ARIF NU 002 SAMARINDA - ROHMAH, AL KHAFIDAH ARIFAH YA NUR ROHMAH; BAHRANI, BAHRANI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) at RA Ma'arif NU 002 Samarinda in an effort to improve the quality of education, and explore how TQM principles are integrated with Islamic values ​​adopted by the institution. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that the institution consistently implements three main principles of TQM, namely customer focus, total involvement, and continuous improvement. The focus on students and parents is reflected in an adaptive and needs-based education service program. Total involvement is realized through the active involvement of all elements of the school in decision-making, as well as teacher capacity building programs. Continuous improvement is carried out through periodic program evaluation and innovation cycles. The uniqueness of the implementation of TQM at RA Ma'arif NU 002 is its success in integrating Islamic values ​​such as amanah, deliberation, ihsan, and justice into the institution's quality culture. These values ​​not only strengthen work ethics, but also form a quality paradigm that is not only technical, but also spiritual. This integration creates an educational ecosystem that is not only superior in management, but also in the formation of religious character. The conclusion of this study shows that TQM can be adapted effectively in the context of Islamic educational institutions, with a value approach as a reinforcement of the implementation of the quality management system.